MODEL KONSEPTUAL SISTEM PANAS BUMI DAERAH “UBL” PROVINSI LAMPUNG DENGAN MENGGUNAKAN DATA LOG BOR DAN GEOKIMIA MANIFESTASI PERMUKAAN: CONCEPTUAL MODEL OF THE “UBL” REGION GEOTHERMAL SYSTEM OF LAMPUNG PROVINCE USING DRILL LOG DATA AND SURFACE MANIFESTATION GEOCHEMICALS - Muhammad Aisy Omar; Fajar Hendrasto; Graniko Reza Utama (Universitas trisakti, 2022)
The UBL area is included in the Tanggamus Regency, Lampung province, with the potential for geothermal resources. The study of geothermal in the UBL area continues to increase along with the existence of geothermal operating areas that have been proven to produce geothermal energy that is capable of being used as a Geothermal Power Plant (PLTP). Therefore, this research was conducted to look in more detail through surface data and subsurface data so that it can provide an overview of the geothermal model in this